2020
DOI: 10.1002/wfp2.12007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetically modified food knowledge, environmental, and food safety concerns on purchase intention of genetically modified food in mediating role of perceived risk: An empirical study in Thailand

Abstract: With the increasing population of world, science has stepped into genetically modified (GM) food. This has been innovated not just to increase the quantity of food but to instill the desired characteristics in a natural food item. Yet, many people are not responding to such GM food positively by considering it unnatural and artificial. The purpose of this research is to assess the impact of environmental consciousness, GM food knowledge and food safety concern on purchasing intention of GM food items in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“… 40 In the same way, researchers also have divided and some of them explained the perceived risks of food safety, health and environmental concerns caused by GM food. Such as Pattanapomgthorn, Sutduean and Keohavong 41 and Pino, Amatulli, De Angelis and Peluso 42 found that GM foods are extended significantly by the dominant scientific methods, which have modified farming techniques that directly or indirectly affect environmental impacts. Pattanapomgthorn, Sutduean and Keohavong 41 also explain that food protection is related to hazards such as impurities, chemical substances, toxins and diet drawbacks and also linked with culture, religion and family.…”
Section: Mediating Effect Of Perceived Risk and Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 In the same way, researchers also have divided and some of them explained the perceived risks of food safety, health and environmental concerns caused by GM food. Such as Pattanapomgthorn, Sutduean and Keohavong 41 and Pino, Amatulli, De Angelis and Peluso 42 found that GM foods are extended significantly by the dominant scientific methods, which have modified farming techniques that directly or indirectly affect environmental impacts. Pattanapomgthorn, Sutduean and Keohavong 41 also explain that food protection is related to hazards such as impurities, chemical substances, toxins and diet drawbacks and also linked with culture, religion and family.…”
Section: Mediating Effect Of Perceived Risk and Benefitsmentioning
confidence: 99%
“…Such as Pattanapomgthorn, Sutduean and Keohavong 41 and Pino, Amatulli, De Angelis and Peluso 42 found that GM foods are extended significantly by the dominant scientific methods, which have modified farming techniques that directly or indirectly affect environmental impacts. Pattanapomgthorn, Sutduean and Keohavong 41 also explain that food protection is related to hazards such as impurities, chemical substances, toxins and diet drawbacks and also linked with culture, religion and family. Therefore, many institutions in the world are working to ensure food safety, health and overcome the environmental concerns.…”
Section: Mediating Effect Of Perceived Risk and Benefitsmentioning
confidence: 99%
“…Consumers' good or bad perceptions of purchasing natural food products are dependent on their perceptions of values received from such a transaction (Garg and Joshi, 2018). The literature examined in the preceding sections reveals that consumer intentions to use food products are inconsistent (Pattanapomgthorn et al, 2020). The presence of individual features that can impact intents to purchase, which could explain these inconsistencies (Saleki et al, 2020;Chakraborty et al, 2019).…”
Section: Attitude As a Moderatormentioning
confidence: 99%
“…Perceived risks in products and services discouraged business intentions and activities (Ariffin et al, 2018;Casidy & Wymer, 2016;Hussain et al, 2017). For example, Pattanapomgthorn et al ( 2020) revealed that perceived risk decreases customers' buying intention toward GM food.…”
Section: Perceived Riskmentioning
confidence: 99%
“…Unlike non-food hazards, food safety can lead to severe foodborne illness; thus, unhygienic conditions and environments can risk consumers (Pattanapomgthorn et al, 2020). Food safety concerns, such as food temperature, hygiene of food handlers, and the environment customers perceive when receiving their food, can determine the perceived risk to their health (Ha et al, 2019;Nam et al, 2019;Nguyen & Huynh, 2018).…”
Section: Perceived Food Safety and Perceived Riskmentioning
confidence: 99%